APPLICATION OF BALANCED SCORECARD (BSC) IN THE SYSTEM OF TRAINING AND RETRAINING OF PERSONNEL FOR THE INFORMATION SOCIETY - D. A. Belyanin (Дискурс)
The article is devoted to the problem of training of personnel to implement the state strategy of building information society in Russia. The article considers the concept of Balanced Scorecard (BSC) as an effective instrument in the system of training and retraining of personnel at digital enterprise. It addresses the questions of forming the fourth perspective of Balanced Scorecard (BSC) "Learning and growth". The stages of formation of "Learning and growth" perspective are considered. The strategic human resource objectives are defined, the analysis of the main human resource indicators is provided. The process of defining the target values of human resource indicators and the process of developing strategic personnel actions are considered. The use of BSC in the system of training and retraining of personnel and improving the efficiency of digital enterprise is considered.